Optically activated shutter using a photo-tunable short-pitch chiral nematic liquid crystal - Morris, S. M.; Qasim, M. M.; Cheng, K. T.; Castles, F.; Ko, D-H.; Gardiner, D. J.; Nosheen, S.; Wilkinson, T. D.; Coles, H. J.; Burgess, C.; Hill, L. (AMER INST PHYSICS, 2013)
We report the demonstration of an optically activated shutter based upon a short-pitch chiral nematic liquid crystal (LC) device sandwiched between crossed polarizers. This LC is comprised of photoactive chiral dopants. In the trans-state, the LC appears dark between crossed polarizers due to the very short pitch. As the pitch is extended through exposure to ultraviolet light, the device becomes transmissive reaching a maximum for a particular value of the pitch. As a result, it is possible to switch between the light and dark states by subjecting the device to visible light so as to cause a cis-trans photo-isomerisation. (C) 2013 AIP Publishing LLC.
Keywords: LIGHT SHUTTERS; COLOR-CHANGE; DOPANTS; REFLECTION; SWITCHES; BANDGAPS; FILTER